Non‐coding regulatory elements: Potential roles in disease and the case of epilepsy. (16th December 2021) - Pagni, Susanna; Mills, James D.; Frankish, Adam; Mudge, Jonathan M.; Sisodiya, Sanjay M.
Abstract: Non‐coding DNA (ncDNA) refers to the portion of the genome that does not code for proteins and accounts for the greatest physical proportion of the human genome. ncDNA includes sequences that are transcribed into RNA molecules, such as ribosomal RNAs (rRNAs), microRNAs (miRNAs), long non‐coding RNAs (lncRNAs) and un‐transcribed sequences that have regulatory functions, including gene promoters and enhancers. Variation in non‐coding regions of the genome have an established role in human disease, with growing evidence from many areas, including several cancers, Parkinson's disease and autism. Here, we review the features and functions of the regulatory elements that are present in the non‐coding genome and the role that these regions have in human disease. We then review the existing research in epilepsy and emphasise the potential value of further exploring non‐coding regulatory elements in epilepsy. In addition, we outline the most widely used techniques for recognising regulatory elements throughout the genome, current methodologies for investigating variation and the main challenges associated with research in the field of non‐coding DNA. Abstract : Non‐coding DNA (ncDNA) includes sequences that have regulatory functions. Here, we review the features of the non‐coding regulatory elements and their role in human disease. We then review the existing research in epilepsy and emphasise the potential value of further exploring non‐coding regulatory elements. We outline the most widely used techniques for recognising regulatory elements throughout the genome, current methodologies for investigating variation and the main challenges associated with research in the field of non‐coding DNA.